Insecticidal and phytotoxic activity of essential oil from Colombian Eryngium foetidum L. (2023)
Eryngium foetidum L. is a biennial herb belonging to the family Apiaceae, which is used extensively as a medicinal plant in most tropical regions. In this research work, the activity of the essential oil (EO) from E. foetidum against the Hyalomma lusitanicum Koch, and its phytotoxicity in germination of seeds of Lolium perenne and Lactuca sativa was studied. E. foetidum EO was isolated by the hydrodistillation technique. Gas chromatography coupled to mass spectrometry (GC-MS) was used to identify the volatile metabolites. Fifteen compounds were found in the E. foetidum EO. The major compounds were E-2-dodecenal (53.0%), trimetilbenzaldehyde (duraldehyde) (14.8%), cyclododecane (4.4%), trans-tetradec-enal (3.9%), decanal (3.6%), and trans-2-dodecen-1-ol (3.0%) and D-limonene (1.5%), respectively. The E. foetidum EO, and two of its individual main compounds (2-dodecenal, and duraldehyde) had low phytotoxic activity when were compared with the percentage of inhibition of germination of the control (carvone), in seeds of L. perenne and L. sativa. The acaricidal activity against Hyalomma lusitanicum was determined using a probit analysis (P>0.05). The essential oil of E. foetidum showed 100% mortality on H. lusitanicum at a concentration of 10 µg µL-1, and LC50 = 4.2 µg µL-1. The results obtained from the essential oil of E. foetidum show a great potential to develop natural biocides for the control of H. lusitanicum due to its chemical composition rich in aldehydes and benzene derivatives, and without adverse phytotoxic effects.